Volume 9: Oil and Gas Applications; Supercritical CO2 Power Cycles; Wind Energy 2017
DOI: 10.1115/gt2017-64475
|View full text |Cite
|
Sign up to set email alerts
|

Parametric Investigation of Gurney Flaps for the Use on Wind Turbine Blades

Abstract: This paper presents a strategy to model the aerodynamic Gurney flap effect on two-dimensional airfoils and subsequently on the rotor blade performance of horizontal axis wind turbines. The first part consists of the parametric investigation of 26 airfoil polar data-sets, derived from different, but comparable, wind tunnel experiments. They are evaluated and processed in terms of the lift and drag increase caused by Gurney flaps in comparison to each Baseline configuration. Consequently, a model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…2b: for GF = 1.5 %c a vortex street is triggered, while for GF = 0.5 %c the wake is shed in a relatively smooth way. In a similar manner, Alber et al (2017) suggest the use of very small GF heights of approximately half the local BL thickness in order to maintain, or even improve, the airfoil L / D ratio of different DU and NACA airfoils.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…2b: for GF = 1.5 %c a vortex street is triggered, while for GF = 0.5 %c the wake is shed in a relatively smooth way. In a similar manner, Alber et al (2017) suggest the use of very small GF heights of approximately half the local BL thickness in order to maintain, or even improve, the airfoil L / D ratio of different DU and NACA airfoils.…”
Section: Introductionmentioning
confidence: 91%
“…Additionally, another GF height of half the local δ is chosen so that the GF configurations consist of GF = 1.0 %c and GF = 0.5 %c. For comparison, the FFA-W3-241 airfoil (th max = 24.1 %c, Re = 12.0 × 10 6 ), which is used in the outer blade region of the DTU 10 MW reference wind turbine (Bak et al, 2013), generates a BL of δ TE ≈ 0.30 %c. As such, the application of GF > 0.30 %c would be likely to cause the L / D ratio to decline, as illustrated in Fig.…”
Section: Gurney Flapsmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, for GF = 1.5 %c a vortex street is triggered while for GF = 0.5 %c the wake is shed in a relatively smooth way. In a similar manner, Alber et al (2017) suggest the use of very small GF-heights of approximately half the local BL thickness in order to maintain, or even improve the airfoil L/D-ratio of different DU and NACA airfoils.…”
Section: Introductionmentioning
confidence: 92%
“…The study of Gurney flaps' implementation and performance has been widely reported, both experimentally and numerically. According to Alber et al [16], who analyzed wind tunnel tests for GFs on nine different airfoils and for different GF heights, GFs' effect on the C L / C D ratio is likely to be favorable as long as small heights are assumed. Moreover, they presented the effect on rotor blades computationally; the results suggest an enhanced power performance between 0.8% and 2.0% for small GF heights.…”
Section: Introductionmentioning
confidence: 99%